2015
DOI: 10.1080/07373937.2015.1036287
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Numerical Simulation of Clays Cracking During Drying

Abstract: During drying or desiccation of clay-type materials, some stresses appear. Usually they are compressional inside of the material and tensional close to the surface. If the tensional stresses exceed the material strength, the clay cracks. This article is devoted to the modeling and numerical simulation of this phenomenon. The proposed model consists of two parts. The mass transfer is described by a simple diffusion equation together with convective boundary conditions. In the mechanical part it is assumed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…3) agree with the accelerated decrease of MC below the value of 0.25 (w/w), which was followed by a slow moisture uptake until 0.30 (w/w). A heterogeneous distribution of moisture content and the compressional and tensional internal forces caused by non-uniform shrinkage during drying, [36] are factors related to a complex change in its microstructure. They may induce softening effects that influences the internal process of moisture diffusion and affects their mechanical properties [37].…”
Section: The Physics Of Drying Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) agree with the accelerated decrease of MC below the value of 0.25 (w/w), which was followed by a slow moisture uptake until 0.30 (w/w). A heterogeneous distribution of moisture content and the compressional and tensional internal forces caused by non-uniform shrinkage during drying, [36] are factors related to a complex change in its microstructure. They may induce softening effects that influences the internal process of moisture diffusion and affects their mechanical properties [37].…”
Section: The Physics Of Drying Kineticsmentioning
confidence: 99%
“…Microscopic variations in structural inhomogeneities as pores, voids, hollows and solid bridge bonds also play a role in evolution of cracks during drying [40]. The repetitive compaction during the previous spheronization step can contribute to originate microcracks, then, propagation may result from an increase in the water suction of the pores inside the pellet due to a change from the solid-liquid state to the liquid-unsaturated solid-state caused by the evaporation process, where air begins to replace the water inside the pores of the pellet [41], the distances between the particles decrease and the material shrinks [36]. Immediately, cracks propagate profusely from the structural inhomogeneities during moisture uptake; as were observed in spherical zeolite granules of millimetersize [40].…”
Section: The Physics Of Drying Kineticsmentioning
confidence: 99%
“…One of the main simplifying assumptions which has been done in many studies dealing with the drying process modeling is neglecting the heat 17 and/or mechanical aspects 7 . Neglecting material properties changes, material deformation and simplified 1D or 2D geometry are the other common simplifying assumptions in drying models.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have been done on drying kinetic and drying induced stresses in 1D geometry, 2D geometry, and axisymmetric geometry . The motivation of the current study is to work with a 3D moist object using a drying model that enables simulation of not only the drying kinetics but also of mechanical stresses accompanying the drying; hence, overcoming problems mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%
“…There are a large number of research works studying the effect of drying conditions on drying induced stresses . A number of studies can be found in the literatures dealing with the influence of material's properties on drying kinetic and drying induced stresses. DeCarlo and Shokri () studied experimentally the effect of salt concentrations on cracking morphology in 3D desiccating clays .…”
Section: Introductionmentioning
confidence: 99%